Faktor-Faktor Yang Mempengaruhi Audit Delay Pada Perusahaan Sektor Properties & Real Estate - Sinaga, Krismando Viktor; Syafira Ulya Firza; Eni Duwita Sigalingging (Owner : Riset dan Jurnal Akuntansi, 2024)
This research is based on the phenomenon of many public companies experiencing long periods of time in publishing their financial reports. This research aims to test the effect of profitability, solvency, firm size, and auditor reputation on audit. In this study, profitability, solvency, firm size, and auditor reputation variables act as independent variables, besides the dependent variable used is audit delay. The sample in this study is properties & real estate companies listed on the IDX in 2021- 2022 with a total sample of 70 samples. The sample selection is based on the purposive sampling method with the criteria and requirements determined by the researcher. The analytical method used in this research is multiple linear regression analysis using SPSS 25 program aid. The results showed that partially variables profitability have a significant negative effect on audit delay and solvency have a negative effect but not significant on audit delay. Meanwhile, the firm size and auditor reputation have a positif but not significant effect on audit delay.